Statistical time energy based damage detection in steel plates using artificial neural networks - Paulraj, Murugesa Pandiyan, Prof. Madya (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/